Identifikasi Partikel Emas Pada Daun Kayu Putih dengan XRF (X-Ray Fluorescence) dan AAS (Atomic Absorption Spectroscopy) Sebagai Indikator Potensial Tambang Emas di Indonesia - Dian Artha Kusumaningtyas; Hanif Khoirudin; Muamila Tami; Mila Utami Sari; Arif Nirsatmanto; Ari Dwi Nugraheni; Fahrudin Nugroho (Postgraduate, University of Mataram, 2022)
Eucalyptus is a plant that is able to absorb gold (Au) particles from the soil and store them in the leaves. Eucalyptus roots have the ability to penetrate the soil of the calcrete zone, which is rich in the mineral calcium (Ca). Calcium is a chemical element with the symbol Ca and atomic number 20. As an alkaline earth metal, calcium is a reactive metal that forms a dark oxide-nitride layer when exposed to air. and contains Au particles as impurities, making this plant a potential natural indicator (biogeochemical) of potential Au metal mining. The Au content in eucalyptus leaves can be determined by using the XRF (X-Ray Fluorescence) instrumentation material analysis method for qualitative analysis and AAS (Atomic Absorption Spectroscopy) for quantitative results. The form of XRF characterization of the intensity versus energy spectrum of certain elements from the XRF analysis results obtained is a spectrum with a peak power of 9.731 keV which indicates the presence of Au metal in the sample. The results obtained qualitatively are the Au metal content in the eucalyptus leaf sample of (9.0 Â± 0.5) ppm. However, the Au metal content in each leaf sample was different. This provides information that Eucalyptus from different plants has the potential to be a biogeochemical indicator of potential Au metal mining in Indonesia